Metal induced self-assembly of designed V-shape protein into 2D wavy supramolecular nanostructure. Issue 1 (27th November 2015) - Qiao, S. P.; Lang, C.; Wang, R. D.; Li, X. M.; Yan, T. F.; Pan, T. Z.; Zhao, L. L.; Fan, X. T.; Zhang, X.; Hou, C. X.; Luo, Q.; Xu, J. Y.; et al.
Abstract : Utilizing V shape proteins, we construct 1D, 2D complicated nanostructures through metal coordination. This provides an approach for designing protein assemblies with distinctive topological morphology. Abstract : In order to understand and imitate the more complex bio-processes and fascinating functions in nature, protein self-assembly has been studied and has attracted more and more interest in recent years. Artificial self-assemblies of proteins have been constructed through many strategies. However, the design of complicated protein self-assemblies utilizing the special profile of building blocks remains a challenge. We herein report linear and 2D nanostructures constructed from a V shape SMAC protein and induced by metal coordination. Zigzag nanowires and wavy 2D nanostructures have been demonstrated by AFM and TEM. The zigzag nanowires can translate to a 2D nanostructure with an excess of metal ions, which reveals the step by step assembly process. Fluorescence and UV/Vis spectra have also been obtained to further study the mechanism and process of self-assembly. Upon the protein nanostructure, fluorescence resonance energy transfer (FRET) could also be detected using fluorescein modified proteins as building blocks. This article provides an approach for designing and controlling self-assembled protein nanostructures with a distinctive topological morphology.